Sustainable Extraction Technology of Fruit and Vegetable Residues as Novel Food Ingredients - Shiqi Zheng; Zhoumei Huang; Li Dong; Daotong Li; Xiaosong Hu; Fang Chen; Chen Ma (Foods)
Background: Fruit and vegetable waste (FVW) is a global waste issue with environmental impacts. It contains valuable compounds such as polysaccharides, polyphenols, proteins, vitamins, pigments, and fatty acids, which can be extracted for food applications. This study aims to review sustainable extraction methods for FVW and its potential in the food industry. Methods: This paper provides an overview of the sources and sustainable methods of high value-added compounds extracted from FVW. Sustainable techniques, including supercritical fluid extraction and ultrasound-assisted extraction, are compared with traditional methods, for their efficiency in extracting high-value compounds from FVW while minimizing environmental impact. Discussions: Sustainable extraction of FVW compounds is sustainable and beneficial for novel food ingredients. However, challenges in scalability and cost need to be addressed for wider adoption in the food sector. Conclusions: Sustainable extraction techniques effectively extract phytochemicals from FVW, preserving bioactivity and reducing environmental load. These methods show promise for sustainable food ingredient development.